“Call Me Judy”: Cross-Cultural Interaction in Asian-American Environment - Effendi, Palupi Paramarta (MOZAIK HUMANIORA, 2024)
This study scrutinizes the cross-cultural interactions in the 2019 Asian-American movie Always Be My Maybe. A notable linguistic feature that diverges across cultures is the honorific system, which varies significantly between Asian and Western contexts. This research analyzes the honorifics employed in the movie using a qualitative approach, grounded in Brown and Levinson’s politeness theory. The findings reveal that, despite the Asian-American setting, the Korean main characters often use the Korean honorific system to address elders, highlighting cultural retention. Additionally, the study underscores that acculturation occurs naturally for individuals living in different cultural environments over time. However, it emphasizes that individuals do not entirely abandon their original culture nor fully adopt the new one. This dynamic is illustrated through the characters’ interactions, where they navigate between Korean and Western addressing systems based on context and relationships. The use of honorifics and politeness strategies plays a crucial role in avoiding misunderstandings and maintaining harmony. Another finding from this study, which is related to the first, shows that acculturation is inevitably encountered by someone who has been living in a different culture for a period of time. This study serves as a case analysis representing the interplay of honorific systems from two cultures, providing insights into sociopragmatic behaviors in cross-cultural settings.